My Lai [videorecording (DVD)] - Goodman, Barak (PBS Distribution, 2010)
The words 'My Lai' are seared into our memories of the Vietnam War, but few know what really happened in the small Vietnamese village on March 16, 1968. Now, drawing on 400 hours of recently discovered audio recordings and new interviews with participants, eye witnesses, and investigators, the complete story can finally be told about one of the most shocking atrocities in modern times, and about lesser-known acts of remarkable courage.